Regulatory T Cell (Treg) Subsets Return in Patients with Refractory Lupus following Stem Cell Transplantation, and TGF-β-Producing CD8+ Treg Cells Are Associated with Immunological Remission of Lupus - Zhang, Li; Bertucci, Anne M; Ramsey-Goldman, Rosalind; Burt, Richard K; Datta, Syamal K (The Journal of immunology (1950), 2009)
Compared with conventional drug therapy, autologous hemopoietic stem cell transplantation (HSCT) can induce very-long-term remission in refractory lupus patients. Herein, we show that in posttransplant patients, both CD4+CD25highFoxP3+ and an unusual CD8+FoxP3+ Treg subset return to levels seen in normal subjects; accompanied by almost complete inhibition of pathogenic T cell response to critical peptide autoepitopes from histones in nucleosomes, the major lupus autoantigen from apoptotic cells. In addition to a stably sustained elevation of FoxP3, posttransplant CD8 T cells also maintained markedly higher expression levels of latency-associated peptide (LAP), CD103, PD-1, PD-L1, and CTLA-4, as compared with pretransplant CD8 T cells that were identically treated by a one-time activation and rest in short-term culture. The posttransplant CD8 regulatory T cells (Treg) have autoantigen-specific and nonspecific suppressive activity, which is contact independent and predominantly TGF-β dependent. By contrast, the pretransplant CD8 T cells have helper activity, which is cell contact dependent. Although CD4+CD25high Treg cells return during clinical remission of conventional drug-treated lupus, the posttransplant patient’s CD8 Treg cells are considerably more potent, and they are absent in drug-treated patients in whom CD4 T cell autoreactivity to nucleosomal epitopes persists even during clinical remission. Therefore, unlike conventional drug therapy, hemopoietic stem cell transplantation generates a newly differentiated population of LAPhighCD103high CD8TGF-β Treg cells, which repairs the Treg deficiency in human lupus to maintain patients in true immunological remission.